The Complex Function of Hsp70 in Metastatic Cancer - Juhasz, Kata (MDPI, 2013)
Elevated expression of the inducible heat shock protein 70 (Hsp70) is known to correlate with poor prognosis in many cancers. Hsp70 confers survival advantage as well as resistance to chemotherapeutic agents, and promotes tumor cell invasion. At the same time, tumor-derived extracellular Hsp70 has been recognized as a “chaperokine”, activating antitumor immunity. In this review we discuss localization dependent functions of Hsp70 in the context of invasive cancer. Understanding the molecular principles of metastasis formation steps, as well as interactions of the tumor cells with the microenvironment and the immune system is essential for fighting metastatic cancer. Although Hsp70 has been implicated in different steps of the metastatic process, the exact mechanisms of its action remain to be explored. Known and potential functions of Hsp70 in controlling or modulating of invasion and metastasis are discussed.